'All Things to All People': 1 Corinthians, Ethnic Flexibility, and Social Identity Theory. (June 2021) - Porter, Christopher A.; Rosner, Brian S.
Since Judge's pioneering 1960 monograph on social engagement in early Christian groups there have been a host of further sociological and social-psychological engagements with ancient texts. One relative newcomer to the biblical research discipline is the socio-cognitive engagement of Social Identity Theory (SIT) and its attendant approaches. This article traces how Social Identity Theory has been applied to the biblical texts, using 1 Corinthians as an exemplary case. We trace the development of social approaches to 1 Corinthians from Theissen's early engagements through to the current applications of SIT to the text. This is followed by a broad overview of the theory and approaches, along with a brief survey of its application to biblical research, and then 1 Corinthians. Finally, we utilize 1 Cor. 9.19-23 for a brief demonstration of the analytical utility of SIT within the social context of the epistle.